Dynamics, outcomes and prerequisites of the first SARS-CoV-2 superspreading event in Germany in February 2020: a cross-sectional epidemiological study. Issue 4 (6th April 2022) - Wessendorf, Lukas; Richter, Enrico; Schulte, Bianca; Schmithausen, Ricarda Maria; Exner, Martin; Lehmann, Nils; Coenen, Martin; Fuhrmann, Christine; Kellings, Angelika; Hüsing, Anika; Jöckel, Karl-Heinz; Streeck, Hendrik
Abstract : Objectives: The first German SARS-CoV-2 outbreak was a superspreading event in Gangelt, North Rhine-Westphalia, during indoor carnival festivities called 'Kappensitzung' (15 February 2020). We determined SARS-CoV-2 RT-PCR positivity rate, SARS-CoV-2-specific antibodies, and analysed the conditions and dynamics of superspreading, including ventilation, setting dimensions, distance from infected persons and behavioural patterns. Design: In a cross-sectional epidemiological study (51 days postevent), participants were asked to give blood, pharyngeal swabs and complete self-administered questionnaires. Setting: The SARS-CoV-2 superspreading event took place during festivities in the small community of Gangelt in February 2020. This 5-hour event included 450 people (6–79 years of age) in a building of 27 m × 13.20 m × 4.20 m. Participants: Out of 450 event participants, 411 volunteered to participate in this study. Primary and secondary outcome measures: Primary outcome: infection status (determined by IgG ELISA). Secondary outcome: symptoms (determined by questionnaire). Results: Overall, 46% (n=186/404) of participants had been infected, and their spatial distribution was associated with proximity to the ventilation system (OR 1.39, 95% CI 0.86 to 2.25). Risk of infection was highly associated with age: children (OR 0.33, 95% CI 0.267 to 0.414) and young adults (age 18–25 years) had a lower risk of infection than older participants (average risk increase of 28% per 10 years). Behavioural differences were also risk associated including time spent outside (OR 0.55, (95% CI 0.33 to 0.91) or smoking (OR 0.32, 95% CI 0.124 to 0.81). Conclusions: Our findings underline the importance of proper indoor ventilation for future events. Lower susceptibility of children/young adults indicates their limited involvement in superspreading.